Rhinovirus C replication is associated with the endoplasmic reticulum and triggers cytopathic effects in an in vitro model of human airway epithelium. - Talita B Gagliardi; Monty E Goldstein; Daniel Song; Kelsey M Gray; Jae W Jung; Maxinne A Ignacio; Kimberly M Stroka; Gregg A Duncan; Margaret A Scull (PLoS Pathogens)
The clinical impact of rhinovirus C (RV-C) is well-documented; yet, the viral life cycle remains poorly defined. Thus, we characterized RV-C15 replication at the single-cell level and its impact on the human airway epithelium (HAE) using a physiologically-relevant in vitro model. RV-C15 replication was restricted to ciliated cells where viral RNA levels peaked at 12 hours post-infection (hpi), correlating with elevated titers in the apical compartment at 24hpi. Notably, infection was associated with a loss of polarized expression of the RV-C receptor, cadherin-related family member 3. Visualization of double-stranded RNA (dsRNA) during RV-C15 replication revealed two distinct replication complex arrangements within the cell, likely corresponding to different time points in infection. To further define RV-C15 replication sites, we analyzed the expression and colocalization of giantin, phosphatidylinositol-4-phosphate, and calnexin with dsRNA. Despite observing Golgi fragmentation by immunofluorescence during RV-C15 infection as previously reported for other RVs, a high ratio of calnexin-dsRNA colocalization implicated the endoplasmic reticulum as the primary site for RV-C15 replication in HAE. RV-C15 infection was also associated with elevated stimulator of interferon genes (STING) expression and the induction of incomplete autophagy, a mechanism used by other RVs to facilitate non-lytic release of progeny virions. Notably, genetic depletion of STING in HAE attenuated RV-C15 and -A16 (but not -B14) replication, corroborating a previously proposed proviral role for STING in some RV infections. Finally, RV-C15 infection resulted in a temporary loss in epithelial barrier integrity and the translocation of tight junction proteins while a reduction in mucociliary clearance indicated cytopathic effects on epithelial function. Together, our findings identify both shared and unique features of RV-C replication compared to related rhinoviruses and define the impact of RV-C on both epithelial cell organization and tissue functionality-aspects of infection that may contribute to pathogenesis in vivo.